Economic factors that affect the financial system of banking in ecuador 2018-2022 (Revista "Boletín el Conuco", 2024)
Objective: Determine if economic factors affect the performance of the banking financial system in Ecuador. The problem lies in the lack of clarity about the relationship between macroeconomic variables and the financial activity of banking institutions in the country. Method: A mixed approach was used that combines economic data from secondary sources and the Pearson correlation model was applied. Results: Although a direct relationship was not found between the analyzed factors and the granting of financial credits, thus rejecting the research hypothesis, significant correlations were revealed between macroeconomic variables and the financial system. A strong correlation stands out between active rates (-0.711), passive rates (0.718), with years and credits (0.978) with deposits. Conclusions: It is concluded that it is crucial to continue investigating these factors to strengthen the stability and development of the financial system in Ecuador, promoting sustainable growth and greater permanence in the Ecuadorian banking sector. The research focuses on analyzing how economic factors affect the banking financial system in Ecuador between 2018 and 2022. It seeks to understand their influence on the stability and performance of the banking sector in the midst of economic challenges
Keywords: Banking; Funding; Placements; Economic factor; Financial System